2012
DOI: 10.1021/jp302975c
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Potentials for Phase Equilibria–United Atom Description of Five- and Six-Membered Cyclic Alkanes and Ethers

Abstract: While the transferable potentials for phase equilibria-united atom (TraPPE-UA) force field has generally been successful at providing parameters that are highly transferable between different molecules, the polarity and polarizability of a given functional group can be significantly perturbed in small cyclic structures, which limits the transferability of parameters obtained for linear molecules. This has motivated us to develop a version of the TraPPE-UA force field specifically for five- and six-membered cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
156
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(163 citation statements)
references
References 61 publications
7
156
0
Order By: Relevance
“…We also consider the original TraPPE model of Keasler et al 28 In this model, as usual in TraPPE force fields, the bond lengths between di↵erent chemical groups are fixed. Monomeric units separated by two bonds interact through a harmonic bending potential with the usual form, with bending force constants taken from the TraPPE-UA force field for n-alkanes and ethers.…”
Section: B United-atom Force Field Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also consider the original TraPPE model of Keasler et al 28 In this model, as usual in TraPPE force fields, the bond lengths between di↵erent chemical groups are fixed. Monomeric units separated by two bonds interact through a harmonic bending potential with the usual form, with bending force constants taken from the TraPPE-UA force field for n-alkanes and ethers.…”
Section: B United-atom Force Field Modelsmentioning
confidence: 99%
“…Finally, Keasler et al 28 developed a new version of the TraPPE-UA force field (Transferable Parameters for Phase Equilibria-United Atoms) specifically for five-and six-membered cyclic alkanes and ethers, including THF. In particular, they took into account that partial charges are molecule specific and thus they were parametrized using liquid-phase dielectric constants.…”
Section: Introductionmentioning
confidence: 99%
“…The previous paper of this series [17] compared the performance of three popular UA alkane models, OPLS-UA [8], GROMOS [10] and TraPPE [11][12][13][14], for predicting hydrophobic solvation, i.e., solvation free energies of alkane solutes in alkane solvents. It was found that all three force-fields showed systematic deviations from experimental data [18,19], with OPLS-UA and GROMOS overestimating the magnitude of solvation (by 15% and 13%, respectively), and TraPPE slightly underestimating it (by 6%) [17].…”
Section: -Introductionmentioning
confidence: 99%
“…However, they tend to perform worse than their all-atom counterparts in predictions of dynamic properties (e.g., diffusion and viscosity) [15] because the coarse-graining of the interaction sites leads to less accurate dynamics. Moreover, the complete neglect of electrostatics and polarization means that they are unable to predict dielectric properties, although all-atom fixed-charge models do not appear to perform much better in this respect [16].The previous paper of this series [17] compared the performance of three popular UA alkane models, OPLS-UA [8], GROMOS [10] and TraPPE [11][12][13][14], for predicting hydrophobic solvation, i.e., solvation free energies of alkane solutes in alkane solvents. It was found that all three force-fields showed systematic deviations from experimental data [18,19], with OPLS-UA and GROMOS overestimating the magnitude of solvation (by 15% and 13%, respectively), and TraPPE slightly underestimating it (by 6%) [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation